Gastrointestinal nematode parasites in Saskatchewan cattle: egg count distributions in beef animals. - Polley, L (1987)
Fecal samples were collected systematically in the spring from cows and yearlings entering, and in the fall from calves leaving, five community pastures in central Saskatchewan. Fecal samples were also collected systematically in the spring from cows entering, and in the fall from calves leaving, an experimental rotational grazing system. Samples were collected from 1398 animals and were examined by a quantitative fecal flotation technique with a sensitivity of ten eggs per gram. Distributions of nematode egg counts for 11 of the 12 cattle populations sampled were well described by a series of negative binomial distributions. A common value of k (a measure of aggregation) could be fitted to the counts from animals of all ages in four of the five community pastures, as well as to the counts from the cows from the fifth community pasture and from the rotational grazing system. A second value of k could be fitted to the counts from the calves from these two pasture. In addition, in three of the community pastures animals in the different age groups had the same mean count.